A Mini-Review of Pharmacological and Psychosocial Interventions for Reducing Irritability Among Youth With ADHD - Breaux, Rosanna; Dunn, Nicholas C.; Swanson, Courtney S.; Larkin, Emma; Waxmonsky, James; Baweja, Raman (Frontiers in Psychiatry, 2022)
Approximately a third of children and adolescents with attention-deficit/hyperactivity disorder (ADHD) experience significant irritability; despite this, no study has reviewed whether interventions for youth with ADHD can improve irritability. This mini review sought to address this gap in the literature by discussing existing pharmacological and psychosocial interventions for irritability among children and adolescents with ADHD. A literature search was conducted in April 2021, with a total of 12 intervention articles identified (six pharmacological, one psychosocial, five combined). Studies were excluded if they did not involve an intervention, a measure of irritability, or the population was not youth with ADHD. Of these articles, two were with an ADHD only sample; seven included ADHD with comorbid disruptive behavior, disruptive mood dysregulation disorder (DMDD), or severe mood dysregulation (SMD); and three included ADHD with comorbid autism spectrum disorder (ASD). Findings suggest that central nervous system stimulants used alone or in combination with behavior therapy are effective at reducing irritability in youth with ADHD only or comorbid ADHD and DMDD/SMD. Less evidence was found for the efficacy of guanfacine and atomoxetine for youth with ADHD only or comorbid ADHD and ASD. Parent training alone or in combination with atomoxetine was found to be effective at reducing irritability in youth with comorbid ADHD and ASD. Future research assessing the efficacy of other psychosocial interventions, particularly cognitive behavioral therapy is necessary, as are randomized trials assessing intervention sequencing and intensity among youth with ADHD. Researchers are advised to utilize well-validated measures of irritability in future research.